The Combustion Of N-Butanol-Diesel Fuel Blends And Its Cycle To Cycle Variability In A Modern Common-Rail Diesel Engine - I. M., Yusri; R., Mamat; Obed M., Ali; M. K., Akasyah; M. K., Kamarulzaman; C. K., Ihsan; H. M., Mahmudul (Asian Research Publishing Network (ARPN), 2016)
The depletion of fossil fuel combine with implications of exhaust emissions is regarded as one of the future challenges towards automotive researches. The used of alcohol fuel blends with conventional diesel fuel has attracted wide attention due to their liquid nature, high oxygen contents and high octane number. In this study the used of 10% butanol blends (Bu10) in a modern common rail diesel engine were investigated by means of their cyclic variations and peak incylinder pressure. The experimental test results showed that Bu10 endure inconsistency in term of the combustion stability as the calculated standard deviation (SD) of peak to peak in-cylinder pressure is greater than the diesel fuel at both BMEP = 1.2 Bar and BMEP = 3.5 Bar. Based on the statistical analysis Bu10 experience less than 2.17% of peak in-cylinder pressure at minimum, median and maximum conditions. For frequency distribution most of Bu10 fall in the range of 61-62 by 42 at BMEP = 1.2 bar, meanwhile at BMEP=3.5 bar 72-73 by 58.